2019
DOI: 10.7567/1882-0786/ab1305
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between depth of basal-plane dislocations and expanded stacking faults by application of forward current to 4H–SiC p-i-n diodes

Abstract: The influence of basal-plane dislocation (BPD) depth on the expansion of single Shockley-type stacking faults (1SSFs) was investigated during the forward-current degradation of 4H–SiC p–i–n diodes. The 1SSF expanded from the BPD converted into a threading edge dislocation (TED) in the substrate. The hole density that was injected into the substrate increased with the stress-current density; therefore, BPDs converted into TEDs at a greater depth caused the expansion of 1SSFs under higher stress-current density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…For example, if a current higher than the targeted maximum value is adopted for screening (acceleration test), BPDs located in a deeper region inside the substrate will be activated and the expansion of 1SSFs, which would never expand at the targeted maximum current, will occur. 420) If such 1SSFs approach the epitaxial layer through expansion during the screening test, they will expand more rapidly at a current below the targeted maximum value, making the tested devices easily prone to degradation. The establishment of an accurate and quick screening method is thus an urgent task.…”
Section: Introduction Of a Recombination-enhancing Layermentioning
confidence: 99%
“…For example, if a current higher than the targeted maximum value is adopted for screening (acceleration test), BPDs located in a deeper region inside the substrate will be activated and the expansion of 1SSFs, which would never expand at the targeted maximum current, will occur. 420) If such 1SSFs approach the epitaxial layer through expansion during the screening test, they will expand more rapidly at a current below the targeted maximum value, making the tested devices easily prone to degradation. The establishment of an accurate and quick screening method is thus an urgent task.…”
Section: Introduction Of a Recombination-enhancing Layermentioning
confidence: 99%
“…BPDs in the substrates expand to 1SSFs when the minority carrier injection from the epitaxial layers is significant. [29][30][31][32][33][34][35] For example, in the MOSFETs with vertical structures based on SiC have p-n diode structures between the source and drain contacts, the p-n diodes temporarily turn on at the initial state of turn-off of the MOSFET during operation in electronic circuits. The turned-on p-n diodes induce the expansion of BPDs in the substrates to 1SSFs.…”
Section: Introductionmentioning
confidence: 99%
“…Shockley-type SFs can be inherited from the seed crystal or originate from the dissociation of basal plane dislocations. , The Frank-type SFs are created by climbing of an out-of-plane displacement, which inserts or removes a Si–C bilayer in 4H-SiC. Frank-type SFs are mostly formed by the 2D nucleation or by the conversion from threading screw dislocations (TSDs) during the single-crystal growth. , Various characterization methods, such as X-ray topography (XRT), photoluminescence (PL), cathodoluminescence (CL), and electroluminescence (EL), have been used to investigate the properties of SFs in 4H-SiC single crystals. Transmission electron microscopy (TEM) observations have revealed that the stacking sequences of Si–C bilayers of Shockley-type SFs include (3, 1), (6, 2), (5, 3), and (4, 4) in Zhdanov’s notation, and Frank-type SFs have the stacking sequences of (4, 1), (4, 2), and (5, 2). The local PL, CL, and EL investigations indicate that the luminescence peaks of SFs in 4H-SiC locate in the range from 420 to 500 nm. ,, The transition between a threading edge dislocation (TED) and a Shockley-type SF as well as the transition between a TSD and a Frank-type SF are also found in XRT, TEM, and EL observations. , However, these technologies mainly concentrate on the nanoscale atomic structures as well as local electronic and optical properties of a SF in 4H-SiC.…”
Section: Introductionmentioning
confidence: 99%